A Review paper on Smart Campus using NFC technology - Patil, Vishal S; Borkar, Tejaswini S; Bhute, Suraj S; Chauhan, Gauri J; Morey, Aparna P (International Journal of Computer Sciences and Engineering, 2019)
The concept of Smart Campus Near Field Communication (NFC) is a current growing process. We know that education is one of the basic need of every individual now-a-days. Running collage with all student and parents as well as faculty with complete communication on one single platform will be a boon for today’s security. the main advantage of a Smart Campus NFC technology is that it provides advance technology to make the campus life easier. By using this technology, we can easily enter data while accessing any class room or equipment in the campus. The Smart Campus Near Field Communication (NFC) is mostly used by people education and is time efficient. This is a motivation for the university to act in a smart way, today’s society will have the opportunity to lead a collage or students, parents and each other in the faculty of communication. The Smart Campus system is focus on a solution such as security and collage management to address the university with Cutting- Edge Technologies called Internet of Things(IoT) and NFC technologies.